2014
DOI: 10.1371/journal.pone.0082341
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a Cross-Reactive Gly m 5 Soy Peptide as Responsible for Hypersensitivity Reactions in a Milk Allergy Mouse Model

Abstract: BackgroundCross-reactivity between soybean allergens and bovine caseins has been previously reported. In this study we aimed to map epitopes of the major soybean allergen Gly m 5 that are co-recognized by casein specific antibodies, and to identify a peptide responsible for the cross-reactivity.MethodsCow's milk protein (CMP)-specific antibodies were used in different immunoassays (immunoblotting, ELISA, ELISA inhibition test) to evaluate the in vitro recognition of soybean proteins (SP). Recombinant Gly m 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Nonetheless, it has been demonstrated that some patients are intolerant to such products, suggesting the cross‐reactivity between soy and cow milk proteins. It was reported that the α‐subunit of beta‐conglycinin (Gly m 5.0101) from the vicilin‐like protein family, the G4 subunit of glycinin (Gly m 6.0401) from legumin‐like proteins, and, more recently, the cysteine protease P34 (Gly m Bd30K) and the globulin P28 (Gly m Bd28K) are involved in cross‐reactivity phenomena with bovine caseins (Rozenfeld and others ; Katz and others ; Smaldini and others ; Curciarello and others ; Candreva and others ; Candreva and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Nonetheless, it has been demonstrated that some patients are intolerant to such products, suggesting the cross‐reactivity between soy and cow milk proteins. It was reported that the α‐subunit of beta‐conglycinin (Gly m 5.0101) from the vicilin‐like protein family, the G4 subunit of glycinin (Gly m 6.0401) from legumin‐like proteins, and, more recently, the cysteine protease P34 (Gly m Bd30K) and the globulin P28 (Gly m Bd28K) are involved in cross‐reactivity phenomena with bovine caseins (Rozenfeld and others ; Katz and others ; Smaldini and others ; Curciarello and others ; Candreva and others ; Candreva and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“… 21 , 22 We have previously shown that Gly m 6 G4 and Gly m 5 are recognized by the IgE antibodies of patients allergic to milk, although the clinical relevance of this finding requires further investigation. 23 , 24 , 25 Taking into account the fact that soybean proteins are ubiquitous, exposure to soybean in patients is difficult to discard. A milk-allergic mouse model was used to overcome this problem, and we previously demonstrated that hypersensitivity reactions were elicited in milk-sensitized animals exposed to total soybean proteins or Gly m 6 G4.…”
Section: Introductionmentioning
confidence: 99%
“…We have used a food allergy mouse model to CMP and characterized several soy allergens that cross-react with caseins. We identified B and T epitopes shared between the main soy allergens and bovine caseins [30][31][32]. Again, only a restricted proportion of milk allergic patients react against soy proteins during restriction diet.…”
Section: Current Treatmentsmentioning
confidence: 92%